Validation of the Quantitative Checklist for Autism in Toddlers in an Italian Clinical Sample of Young Children With Autism and Other Developmental Disorders - Ruta, Liliana; Chiarotti, Flavia; Arduino, Giuseppe Maurizio; Apicella, Fabio; Leonardi, Elisa; Maggio, Roberta; Carrozza, Cristina; Chericoni, Natasha; Costanzo, Valeria; Turco, Nazarena; Tartarisco, Gennaro; Gagliano, Antonella; et al. (Frontiers in Psychiatry, 2019)
Background The Q-CHAT is parent-report screening questionnaire for detecting threshold and sub-threshold autistic features in toddlers. The Q-CHAT is a dimensional measure, normally distributed in the general population sample and able to differentiate between a group of children with a diagnosis of autism and unselected toddlers. Objectives We aim to investigate the psychometric properties, score distribution and external validity of the Q-CHAT in an Italian clinical sample of young children with autism versus children with developmental delay and typically developing children. Method N=126 typically developing children (TD), n=139 children with autism and n=50 children presenting developmental delay (DD) were administered the Q-CHAT. Standardized measures of cognitive functions, language and behaviours were also obtained. Results The Q-CHAT scores were normally distributed, demonstrated adequate internal consistency and good item to total score correlations. The mean Q-CHAT score in the autism group was significantly higher than those found in the DD sample and TD children respectively. No difference on the mean Q-CHAT score between DD and TD children was found. The accuracy of the Q-CHAT to discriminate between autism and TD was very good. Two different cut-points (27 and 31 respectively) maximized sensitivity and specificity for autism versus TD and DD respectively. Finally, higher Q-CHAT scores were correlated with lower language and social communication skills. Conclusions In clinical settings, the Q-CHAT demonstrated good psychometric properties and external validity, to discriminate autism children not just from children with typical development but also from children with developmental delay.